V346 Nor: The Post-outburst Life of a Peculiar Young Eruptive Star - Kóspál, Á.; Szabó, Zs. M.; Ábrahám, P.; Kraus, S.; Takami, M.; Lucas, P. W.; Contreras Peña, C.; Udalski, A. (The Astrophysical journal, 2020)
FU Orionis-type objects (FUors) are young low-mass stars undergoing powerful accretion outbursts. The increased accretion is often accompanied by collimated jets and energetic, large-scale molecular outflows. The extra heating during the outburst may also induce detectable geometrical, chemical, and mineralogical changes in the circumstellar material, affecting possible planet formation around these objects. V346 Nor is a southern FUor with peculiar spectral characteristics. Decades after the beginning of its outburst, it unexpectedly underwent a fading event around 2010 due to a decrease in the mass accretion rate onto the star by at least two orders of magnitude. Here we present optical and near-infrared photometry and spectroscopy obtained after the minimum. Our light curves show a gradual re-brightening of V346 Nor, with its Ks-band brightness only 1.5 mag below the outburst brightness level. Our Very Large Telescope (VLT)/XSHOOTER spectroscopic observations display several strong forbidden emission lines toward the source from various metals and molecular hydrogen, suggesting the launch of a new jet. Our N-band spectrum obtained with VLT/VISIR outlines a deeper silicate absorption feature than before, indicating that the geometry of the circumstellar medium has changed in the post-outburst period compared to peak brightness.